Capitalist development and economism in East Asia : the rise of Hong Kong, Singapore, Taiwan, and South Korea - Li, Kui Wai (Routledge studies in the growth economies of Asia ;, 2003)
Taking a conceptual approach, this book studies the economic development of the four East Asian economies since 1950. This work will be of interest to scholars in East Asian economics, and those interested in modern economic development.